Exosomes loaded with the anti-cancer molecule mir-1-3p inhibit intrapulmonary colonization and growth of human esophageal squamous carcinoma cells - Yanmei Yu; Bingjie Jin; Ruzhen Jia; Lei Shi; Yong Chen; Jian Ge; Changqin Xu (Journal of Translational Medicine)
Abstract Background The overall prognosis of patients with esophageal cancer (EC) is extremely poor. There is an urgent need to develop innovative therapeutic strategies. This study will investigate the anti-cancer effects of exosomes loaded with specific anti-cancer microRNAs in vivo and in vitro. Methods Specific miRNAs that were significantly down-regulated in EC tissues were screened using the miRNAs profiling data of human EC tissue samples in TCGA, and the role of their exogenous expression in the proliferation and migration of human EC cell lines, KYSE150 and Eca109, were detected using CCK-8 and Transwell assays. Exosomes were loaded with miRNAs using electroporation. Results The expression of miR-1-3p was significantly down-regulated in human EC tissues with potential anti-cancer effects. Exosomes loaded with miR-1-3p significantly inhibited the proliferation, migration and invasion of KYSE150 and Eca109 cells in vitro, as well as the intrapulmonary colonization and growth of KYSE150 cells in vivo. In addition, miR-1-3p could directly bind to the 3’UTR of the transcription factor E2F5 mRNA, down-regulate the protein expression of E2F5, and inhibit the activation of the MAPK/ERK signaling pathway. Conclusion Exosomes loaded with miR-1-3p may be applicable to the treatment of EC.